Hemodynamic Attenuation During Tracheal Intubation: A Randomized Comparative Analysis of Video vs. Direct Laryngoscopy in Adult Elective Surgery - Imam Safi'i; Arie Zainul Fatoni; Taufiq Agus Siswagama; Ahmad Feza Fadhlurrahman (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Laryngoscopy and tracheal intubation inevitably trigger a sympathoadrenal response, manifesting as tachycardia and hypertension. While video laryngoscopy (VL) offers improved glottic visualization compared to direct laryngoscopy (DL), its efficacy in specifically attenuating this hemodynamic stress remains a subject of debate. This study investigates whether VL provides superior hemodynamic stability during the critical post-intubation period by analyzing the rate pressure product (RPP) and temporal hemodynamic interactions. Methods: In this prospective, single-blind, randomized controlled trial, 40 adult patients (ASA I-II) undergoing elective surgery were allocated to either Group VL (GlideScope, n=20) or Group DL (Macintosh, n=20). Anesthesia was strictly standardized with Fentanyl 2 mcg/kg, Propofol 2 mg/kg, and Atracurium 0.5 mg/kg. Hemodynamic parameters, including systolic blood pressure (SBP), mean arterial pressure (MAP), and heart rate (HR), were recorded at baseline (T0) and at 1 (T1), 2 (T2), and 5 (T5) minutes post-intubation. The primary analysis utilized a general linear model (Repeated Measures ANOVA) to assess Time-Group interactions, corrected for sphericity. Results: Demographics were homogeneous between groups. A significant Time-Group interaction was observed for MAP (p less than 0.001), indicating a blunted pressor response curve in the VL group. Heart Rate at 1-minute post-intubation was significantly lower in Group VL (75.45 plus or minus 11.23 bpm) compared to Group DL (90.15 plus or minus 15.22 bpm; p equals 0.001). Analysis of the rate pressure product revealed that Group DL approached ischemic thresholds, whereas Group VL maintained significantly lower myocardial workload at minutes 1 and 2 (p less than 0.01). Conclusion: Video laryngoscopy significantly attenuates the reflex tachycardia and arterial pressure surge associated with tracheal intubation compared to direct laryngoscopy. VL is recommended to minimize cardiovascular stress in susceptible surgical populations.